The Aesthetics of Hermann Cohen and the Aesthetics of Mikhail Bakhtin: Conceptual Borrowings and their Rethinking - Yudin, Alexander (Sententiae, 2014)
The article deals with the comparative analysis of philosophic and aesthetic positions of H. Cohen and early M. M. Bakhtin. It considers in detail the place of configuration of concepts of completion and aesthetic love (borrowed by Bakhtin from Gohen’s aesthetics) in the aesthetics of each thinker. It shows the radical rethinking of the meaning and contents of these notions and reaccentuating their place in Bakhtin’s aesthetics particularly on connection with the question of relation between art and religion where thinkers take opposed positions, and also in connection with general Bakhtin’s philosophic provisions, treating being as interaction between two consciousnesses. It is concluded that this rethinking conditioned by Bakhtin’s surmounting of transcendental approach in philosophy and going over from philosophy of consciousness to philosophy of being, and in aesthetics – from aesthetics of consciousnesses to aesthetics of event.